Pacifier Use and Its Influence on Pediatric Malocclusion: A Scoping Review of Emerging Evidence and Developmental Impacts - Man Hung; Jacob Marx; Corban Ward; Connor Schwartz (Dentistry Journal)
Background/Objectives: Pacifier use is a widespread soothing practice during infancy, but extended use has been linked to adverse dental outcomes, particularly malocclusion. This review aimed to evaluate the association between pacifier use and dental developmental issues in infants and toddlers and to identify key influencing factors. Methods: A scoping review using PubMed, Scopus, Web of Science, and Dentistry and Oral Sciences Source was performed. Peer-reviewed, full-text articles published in English between 2014 and 2024 were screened by two independent reviewers using predefined criteria. Eligible studies were thematically analyzed. Results: From 262 records, 35 studies met the inclusion criteria. Pacifier use was consistently associated with an increased prevalence of malocclusions, including anterior open bite, posterior crossbite, and overjet. The risk and severity of dental issues were strongly influenced by the duration, frequency, and intensity of pacifier use. Prolonged use beyond three years significantly increased the likelihood of structural changes requiring intervention. Conclusion: There is strong evidence linking pacifier use to negative dental developmental outcomes, particularly when use is prolonged or frequent. Early intervention, caregiver education, and timely weaning are critical to minimizing long-term oral health risks. Future research should explore pacifier design, objective measures of use, and how socioeconomic factors may influence pacifier use patterns and oral health outcomes. Understanding these relationships can support the development of more targeted and equitable prevention strategies.